Pengembangan Media Pembelajaran Berbasis GeoGebra Untuk Meningkatkan Motivasi Belajar dan Representasi Matematis Siswa di SMA Negeri 1 Lembar - Mawarni, Mawarni; Ahmad Muzaki; Ade Kurniawan (Jurnal Kependidikan Ki Hajar Dewantara, 2024)
This research This research aims to produce a product in the form of valid, practical and effective media from GeoGebra-based learning media in increasing students' learning motivation and mathematical representation at SMA Negeri 1sheet. This type of research is development research with the ADDIE model. The population used in this research was class XI MIPA 3 students, namely 31 students with a total sample of 6 students. Research data was obtained using learning media validation questionnaires, validation of test instruments, teacher and student responses, as well as students' mathematical representation tests in the form of pre-test and post-test questions. Based on the assessment results from media experts and material experts, it shows that the media developed is included in the "Very Valid" criteria because it meets the requirements of media experts and material experts. The validity of learning media based on the results of media expert assessments is in the very good category with an average value of 43.5 and a percentage of 87%. The validity of the test instrument based on the results of the material expert's assessment is at very high criteria with an average of 43 and a percentage of 96%. The practicality of the learning media developed based on the results of teacher response questionnaire analysis is in very good criteria with an average score of 4.67 and a percentage of 93.33% and student responses are in very good criteria with an average score of 49.4 and a percentage of 98% . The effectiveness of the learning media developed based on limited trial activities with 6 students, obtained that students' classical completeness in answering post test questions after using the learning media was 84.72% with a KKM of 75. From the results of this research, it can be concluded that GeoGebra-based learning media is very valid , practical and effective in increasing students' learning motivation and mathematical representation at SMA Negeri 1 Lembar.